Adapting sanitary inspections for the monitoring of small drinking water supplies in Iceland. (28th April 2022) - King, R.; Gunnarsdottir, M. J.; Narfason, Þ.; Hjaltadóttir, S.; Sigurðsson, Á.; Herschan, J.; Gardarsson, S. M.; McKeown, R. M.; Pond, K.
Abstract: Sanitary inspections (SIs) are checklists of questions used to identify actual and potential sources and pathways of drinking water contamination. Though the importance of SI adaptation to local contexts is widely acknowledged, there is currently limited guidance on how this should be undertaken in practice. During this research, World Health Organization (WHO) draft template SI forms for spring and borehole supplies were adapted for use in Iceland based on a series of desk reviews and field tests, an approach which may guide other future SI adaptation processes. SI results were collected from 25 spring supplies and nine borehole supplies in three regions of Iceland using adapted SI forms. These results were combined with 10-year historical water quality data from the same supplies to explore potential relationships between both data sets. Binary logistic regression test results indicated a statistically significant association ( P = 0.025; odds ratio (OR) 1.864, 95% CI 1.080–3.220) between SI Question 3 ( Does ponding from surface water occur around the spring/borehole? ) receiving a 'High' risk level assignment and at least one historical incidence of water quality noncompliance for the parameters heterotrophic plate count 22 °C, total coliforms, Escherichia coli, and turbidity at the same supply. The significant modifications applied to the starting template during the testing and development of the Icelandic SI form emphasises the importance of a robust adaptation process to ensure SI forms are appropriate for the local context. Results from the analysis of SI and water quality test results demonstrated the potential for these data sets to identify the primary risks at a supply. This information may then be used to direct remedial actions, especially when the amount of relevant data increases over time. HIGHLIGHTS: Development of an approach for adapting template drinking water SI forms to a local context. Analysis of the relationship between current and historical water quality test results and SI results. Demonstration of a statistical approach to link water quality test results' noncompliance and the presence of individual SI risk factors. Graphical Abstract